Novelties in Trichomanes L. from Colombia - Rojas Alvarado, Alexander (2009)
I describe Tricomanes murilloanum A. Rojas a new species from Colombia. The new species is characterized by monomorphic fronds with only the apical pinnae pairs fertile. Additionally, Trichomanes egleri P.G. Windisch is reported as a new record for the country.